Influence of Framing and Graphic Format on Comprehension of Risk Information among American Indian Tribal College Students - Sprague, Debra (2012)
We evaluated methods for presenting risk information by administering 6 versions of an anonymous survey to 489 American Indian tribal college students. All surveys presented identical numeric information, but framing varied. Half expressed prevention benefits as relative risk reduction, half as absolute risk reduction. One-third of surveys used text to describe prevention benefits; 1/3 used text plus bar graph; 1/3 used text plus modified bar graph incorporating a culturally tailored image. The odds ratio (OR) for correct risk interpretation for absolute risk framing vs. relative risk framing was 1.40 (95% CI=1.01, 1.93). The OR for correct interpretation of text plus bar graph vs. text only was 2.16 (95% CI=1.46, 3.19); OR for text plus culturally tailored bar graph vs. text only was 1.72 (95% CI=1.14, 2.60). Risk information including a bar graph was better understood than text-only information; a culturally tailored graph was no more effective than a standard graph.